ANALISA PENGARUH pH TERHADAP PENYERAPAN NUTRISI DAN PERTUMBUHAN BAWANG MERAH (Allium cepa L. var. Aggregatum) KABUPATEN ENREKANG - Anita Rahman; Andi Azrarul Amri; Ilmiani Rusdin; Hinayah Aulia Arifin; Hardika Musfrianto (Percetakan Umi Toaha Makassar, 2026)
This research aims to analyze the effect of soil pH on nutrient absorption and growth of shallots (Allium cepa L. var. Aggregatum) in Enrekang Regency, focusing on soil pH parameters and Nitrogen (N), Phosphorus (P), and Potassium (K) content. Shallots are an important commodity in Indonesia, including in Enrekang Regency, so understanding the factors that influence their growth is essential. This study uses pH and NPK soil analysis on several different land samples, with soil pH ranging from 7.010 to 7.280, nitrogen content from 0.056% to 0.140%, phosphorus from 11.611 to 12.538 mg/kg, and potassium from 5.027 to 11.882 mg/kg. The results indicate that neutral to slightly alkaline soil pH supports good macro-nutrient absorption, such as nitrogen, phosphorus, and potassium; however, there is potential for reduced micro-nutrient availability at higher pH levels. Higher nitrogen levels enhance vegetative growth, while phosphorus and potassium contribute significantly to bulb formation and harvest quality. In conclusion, the optimal soil pH for shallot growth in Enrekang Regency ranges from neutral to slightly alkaline, with adequate NPK levels to support maximum bulb production.